Pengaruh Penutupan-Balik Tak-Sinkron terhadap Generator Induksi 3-Fase dalam Skema Pembangkitan Tersebar - M. Isnaeni B. S.; F. Danang Wijaya; Eka Firmansyah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Small and medium-scale plants connected to the distribution line form a distributed generation (DG) system. Unsynchronized reclosing, due to the operation of a recloser, is an important issue in DG systems. In this paper, simulations of typical DG system are performed to show the effect of unsynchronized reclosing. The simulation results show that unsynchronized reclosing causes the generator to experience over speed, over and under voltage, and over current, which can damage or reduce the life of the generator. A permanent short circuit that causes the contact of recloser to open and close repeatedly has a worse effect than a temporary short circuit. Opening the circuit breaker at point of common coupling with the installation of dummy load can reduce the bad effect of unsynchronized reclosing.